La homologación de remuneraciones contenida en el art. 53° de la ley 23733 y su reconocimiento a los docentes universitarios cesantes y jubilados - Palacios Castillo, Patricia Roxana (2011)
The development of the present research is distributed in four parts, these being: the Methodological Framework, the Theoretical Framework, the Research Development and the Practical Case in particular. It also includes nine chapters, of which five refer to the theoretical framework addressed and four to the remaining chapters, related to the development of the Research and the respective case study. In the first part, the Methodological Framework is developed framed in the background of the Homologation of Remunerations as well as in the approach of the thesis problem, its motivation and justification, the hypothesis, the analysis of its variables and indicators. In the second part, we have the Normative Theory Framework the same as supporting the hypothesis formulated, is developed in five chapters; The first being that of Legal Security as a fundamental principle of the legal order of a State; The second, the knowledge of the legal norm and the theory of legal interpretation as a subsidiary method of unraveling the meaning of its content; The third, the validity, validity and effectiveness of legal rules as valuable starting points for strengthening the principle of legal certainty; The third, the rights acquired and the inalienability of rights as irrefutable expressions of the principle of legal certainty; And finally, the fifth, entitled jurisdictional function, due process and effective jurisdictional protection as fundamental requirements of the constitutional and democratic state of law. In the third part, the investigation is carried out, consisting of the study and comparative analysis of 5 judgments issued by the Constitutional Court regarding the recognition of the right dealt with, as well as 28 judicial files on cases of homologation of remunerations followed by unemployed and retired persons Of university teaching; Study and analysis that besides being object of discussion, includes additionally a test and verification of the hypothesis raised. In the fourth part, a special chapter is contemplated, referring to the development of the practical case whose content rests in Judgment No. 00023-2007-PI / TC, issued by the Constitutional Court and the analysis of its effects on the subject matter of investigation. Finally, the pertinent conclusions and recommendations are established, which in the future must be taken into account not only for the purpose of recognizing the right of homologation, but also to establish the limits of competence assigned to both the Constitutional Court and the Judiciary